Cyclic loading of model silicone elastomer samples with regard to the failure of silicone breast implants - Lämmlein, Michael; Schubert, Dirk W. (Nordic Polymer Days, 2015)

Cyclic loading of model silicone elastomer samples with regard to the failure of silicone breast implants - Schubert, Dirk W.; Lämmlein, Michael (14th Bayreuth Polymer Symposium, 2015)

Cyclic loading of model silicone elastomer samples with regard to the failure of silicone breast implants - Schubert, Dirk W.; Lämmlein, Michael; von Hanstein, Harald (Polymer Testing, 2018)
It is estimated that 15.000 to 20.000 breast augmentations are performed annually in Germany and several million worldwide. To obtain better knowledge of the reason for and the time of a possible failure of the implant shell, it is important to acquire information regarding the stability and durability of the material used and the associated failure criteria. The mechanical properties of silicone elastomers have therefore been investigated with regard to breast implants. Sample strips of the elastomer of various thicknesses were prepared and exposed to a cyclic bending load for a number of load cycles. Tensile specimens were punched out according to a defined pattern from the preloaded sample strips and tested with regard to their tensile properties, particularly the influence of cyclic loading on the stress at break. However, hence quality of a silicone implant depends not only on the strength of the material, but also on the spatial variation in the mechanical properties, and the quality of the silicone samples was also assessed in terms of the characteristic stress at break and the Weibull modulus, applying Weibull statistics to the tensile test results. The study revealed that the characteristic stress at break remained constant with increasing number of load cycles, but that the Weibull modulus decreased during the first 10.000 cycles exponentially to a critical leve
Keywords: Failure; mapping; mechanical properties; silicone breast implants

Cyclic Loading Of Silicone Breast Implatns Influence On The Failure Statistics - A Model Study - Schubert, Dirk W.; Lämmlein, Michael; Horch, Raymund E. (Book of Abstracts, 2016)

Evaluation and optimisation of the melt-electrospinning process for selected polypropylene additive compounds - Daenicke, Jonas; Schubert, Dirk W.; Lämmlein, Michael; Steinhübl, Felix (Polymertec18, 2018)

Revealing key parameters to minimize the diameter of polypropylene fibers produced in the melt electrospinning process - Daenicke, Jonas; Lämmlein, Michael; Steinhübl, Felix; Schubert, Dirk W. (e-polymers, 2019)
This study deals with the subject of optimizing the melt electrospinning process of polypropylene with the aim of producing nanoscale fibers. A feasibility study with two polypropylene types and different additives to adapt the material composition is performed. The polypropylene types are of different molar masses to adapt the viscosity to the process. The used additives, sodium stearate and Irgastat® P 16, have a positive effect on the electrical conductivity of the polymer melt. In addition, process parameter optimization is done by varying the climate chamber temperature, using different collector voltages and varying the nozzle-collector distance. A strong influence of the climate chamber temperature has been proven and leads to a desired temperature of 100°C. The fiber diameter is dependent on process parameters, material melt viscosity and electrical conductivity. With optimized process and material parameters, the fiber diameter could be minimized to a median value of 210 n
Keywords: melt electrospinning; polypropylene; sodium stearate; nanofibers; process optimizing